2011
DOI: 10.1007/s13593-011-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher yield, profit and soil quality from organic farming of elephant foot yam

Abstract: Alternative agricultural systems, like organic farming, that are less chemical intensive, less exploitative and environment friendly are gaining popularity. Elephant foot yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) is an important starchy tuberous vegetable with high nutritive and medicinal values. Since information on the organic farming of tuberous vegetables is scanty, field experiments were conducted in this crop at the Central Tuber Crops Research Institute, India, over a 5-year period. The impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…In conjunction with physical fertility, we consistently observed better soil chemical fertility under organic farming practices, which has also been reported by others (Singh et al, 2003;Blaise et al, 2004;Kaur et al, 2005;Davies and Lennartsson, 2006;Fließbach et al, 2007;Ramesh et al, 2009;Singh et al, 2009;Suja et al, 2012;Yadav et al, 2013;Wang et al, 2016). In support of this, SOC (or SOM), available forms of major nutrients (N, P, and K), micronutrients (Fe, Zn, Mn, Cu), and CEC were 30%, 16-18%, 2-11%, and 12% greater in organic systems than in the conventional systems at 0 DAT (Tab.…”
Section: Long-term Effect Of Organic Vs Conventional Farmingsupporting
confidence: 90%
See 1 more Smart Citation
“…In conjunction with physical fertility, we consistently observed better soil chemical fertility under organic farming practices, which has also been reported by others (Singh et al, 2003;Blaise et al, 2004;Kaur et al, 2005;Davies and Lennartsson, 2006;Fließbach et al, 2007;Ramesh et al, 2009;Singh et al, 2009;Suja et al, 2012;Yadav et al, 2013;Wang et al, 2016). In support of this, SOC (or SOM), available forms of major nutrients (N, P, and K), micronutrients (Fe, Zn, Mn, Cu), and CEC were 30%, 16-18%, 2-11%, and 12% greater in organic systems than in the conventional systems at 0 DAT (Tab.…”
Section: Long-term Effect Of Organic Vs Conventional Farmingsupporting
confidence: 90%
“…However, several authors disputed this argument and emphasized that reduced nutrient loss (and thus eutrophication of downstream water body) is a co-benefit of organic agriculture systems (Blaise et al, 2004;Wagner et al, 2007;Wuddivira et al, 2009;Soinne et al, 2014;Wang et al, 2016). Moreover, Suja et al (2012) and Askegaard and Eriksen (2007) observed higher available (i.e., potentially mineralizable) N concentrations in organic systems resulting from the substantial input of N from different organic manures including green manures and legumes that release N in synchrony with the plant demand and reduce N loss through leaching and volatilization.…”
Section: Introductionmentioning
confidence: 99%
“…2011;Schmutz et al 2011;Suja et al 2012). Indeed, the largest determinant of profitability was found to be the crop type, location, and price premiums (Kaval 2004).…”
Section: A Yield and Profitabilitymentioning
confidence: 96%
“…Suweg can also be used for traditional medicinal including to treat bronchitis, asthma and dysentery, and ailment for poisonous snake bite (Ramanathan et al 2014;Girardi et al 2015;Dharmadasa et al 2016). There are various methods of management system for suweg, but in general, it can be divided into two systems: grow naturally and being cultivated (Anil et al 2011;Suja et al 2012). For example, Mutaqin et al (2020) mentions that suweg plants grow in West Java are found in several types of agroecosystems, such as home garden, garden, rice field, and pond edge, and grows wild in forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%